Pengaruh Smart Digital Content Marketing Terhadap Keputusan Pembelian Konsumen Millennial Aneka Sport Malang - Innda Indarti; Nurhajati Nurhajati; Siti Asiyah (UNIVERSITAS ISLAM MALANG, 2020)
AbstractThe purpose of this research is to determine the effect of Smart Digital Content Marketing on Consumer Purchasing Decisions Millennial Aneka Sport Malang. This research is an explanatory research using a quantitative approach. The sample used was 100 respondents, namely millennial consumers who had bought shoes at Aneka Sport Malang and followed the @anekasportmalang account. The sampling technique uses purposive sampling method. Data collection by distributing questionnaires that have been tested for validity and reliability. Data analysis uses Multiple Linear Regression. The results showed that simultaneously there was a significant influence between the quality of information, celebrity endorsers, and sales promotions on the purchasing decisions of millennial consumers in Aneka Sport Malang. While partially (t test) shows the quality of information (X1) and celebrity endorser (X2) has no significant effect on purchasing decisions, while the sales promotion variable has a significant effect on purchasing decisions. Keywords : Buying diecision, information quality, celebrity endorser, sales promotion.